Investigating the Language Choice of Acehnese Intermarriage Couples in the Home Domain - Zulfadli A. Aziz; Bukhari Daud; Windasari Windasari (Proceedings of AICS - Social Sciences, 2016)
This study aimed at investigating Acehnese intermarriage couples choosing Bahasa Indonesia as medium of communication in the home domain and discovering the influences of their language choice on the survival of their mother tongues. Interview guide and questionnaire were applied as the instruments in this qualitative study which was conducted in Banda Aceh with five Acehnese intermarriage couples who use Bahasa Indonesia to interact in the home domain. Results of interview showed that there were some reasons those couples prefer to Bahasa Indonesia which are: (1) to accommodate spouse; (2) to be convenient; (3) to expand social network; (4) Bahasa Indonesia is community language; (5) Bahasa Indonesia is the national language; (6) Bahasa Indonesia is the medium of instruction; (7) Bahasa Indonesia is the dominant language; (8) Bahasa Indonesia is a neutral choice; (9) the couples are less motivated to use the indigenous languages. In addition, the results of questionnaire revealed that the intermarriage couples’ language choice might promote linguistic suicide; that is, the parents do not pass their mother tongues to the children. The linguistic suicide may cause the children to own Bahasa Indonesia as their first language or mother tongue resulting in an inability to own their parents’ mother tongues